Biochemical response in cattle vaccinated with Bm95 recombinant Vaccine - V. K. Pal,; V.M. Gawali,; S.K. Rewani,; Jaswant Singh,; S.S.Sengar, (Journal of Livestock Biodiversity, 2025)
Twelve healthy crossbred cattle divided into two groups (A and B) of six animals in each groups. Engorged adult Boophilus microplus female ticks were reared for hatching and larval emergence. Bm95 recombinant tick antigen was obtained from Indian Immunological Ltd., Hyderabad, India. Group A was inoculated with 1 ml of  antigen on zero day and second dose in the same amount on 15 day after primary dose and group B kept as  unvaccinated control. All animals were challenged with larval ticks on 30 day, 70 day and 120 day post vaccination. Blood samples were collected on zero day and weekly interval till one month and then fortnightly up to 5 months. Globulin, Albumin and Total serum protein (TSP) values were signi icant (P